(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Uremic stomatitis is one of the serious pathologies that occurs in patients with chronic renal failure (CRF) , which develops as a result of the effect of uremic toxins on the oral mucosa. Against the background of CRF, metabolic disorders occur in the body, as a result of which toxic substances have a negative effect on the skin, mucous membranes and internal organs. This article analyzes in detail the mechanisms of pathogenesis, clinical manifestations and stages of uremic stomatitis. Diagnostic methods, including laboratory and instrumental examinations, methods for assessing the state of humoral and cellular immunity, are also considered. Information is provided on modern treatment methods, in particular, drug therapy, physiotherapeutic procedures and innovative approaches. The results of the study are of significant scientific and practical importance in the development of strategies for early detection and effective treatment of uremic stomatitis.